PENGARUH PENDALAMAN TEORI TERHADAP PENULISAN ARTIKEL ILMIAH (STUDI: MAHASISWA PENDIDIKAN EKONOMI UNIMED STAMBUK 2023) - Sinaga, Epelima; Siburian, Marshanda; Situmorang, Cheresentia; Lita Br Sitepu, Agnes Dea; Hutasoit, Era Sulastri (Yayasan Education and Social Center, 2024)
Writing quality scientific articles requires a deep understanding of theory as a basis for analysis and argument. This research aims to examine the influence of theoretical deepening on the quality of writing scientific articles among Economic Education students at Medan State University (UNIMED) Stambuk 2023. Through a quantitative approach, data was collected using a questionnaire that measures understanding of theory, as well as the quality of students' writing of scientific articles. The results of the research show that deepening theory has a significant influence on the quality of writing scientific articles, where students who have a deeper understanding of theory tend to produce articles that are more structured, argumentative and can be scientifically justified. This research provides guidance for researchers and academics in improving the quality of scientific articles through deepening theory.